Implementation of Positive Parenting In Early Childhoods’ Families During The Learning From Home Program - Rahayu, Septi; Nurhayati, Sri (Universitas Nusantara PGRI Kediri, 2023)
The article discusses the importance of positive parenting during the COVID-19 pandemic, particularly in the context of early childhood online learning from home. This study aims to provide empirical data on the implementation of positive parenting in Bandung City, Indonesia, during the learning from home program in early childhood families. The study employs qualitative methods with a case study approach and descriptive data analysis. The data for this study were obtained through direct interviews with the study's subjects, namely the parents of two children aged 5 and 6 years old. The results showed that positive parenting at home is done by enforcing certain principles without easing the child's load. Positive parenting is imparted to children based on regular routines, and the implementation of positive parenting during home learning is by establishing family-wide norms. The study highlights the importance of providing parents with support and education to help them develop positive parenting skills, which is especially critical during the COVID-19 pandemic. Positive parenting can help create a nurturing environment that supports a child's emotional and social development and reduces negative behaviors such as aggression and delinquency.